An analysis of the existence of the Authority of the Regional Representative Council Against Amendments to the Constitution of the Republic of Indonesia Year 1945 Article 22d Constitutional Law in the Perspective of Islam - Eka Cahya Wardhani (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research is a form of assessment authority of the Regional Representative Council Republic of Indonesia (DPD RI) as a new state agency of Indonesia Constitutional Structure which is the result of the 3rd amendment to the Constitution of 1945. This study aims to (1) know howthe existence of the authority of the Regional Representative Council Republic of Indonesia in the parliamentary system in Indonesia post third amandemenUUD 1945 Article 22D and (2) determine how the authority of the Regional Legislative Assembly of Republic Indonesia d natural analysis of constitutional law I slam. This research is a form of library research that emphasizes a normative juridical approach, namely a review of the legislation which is the focus of this research on the aspects of the existence of the authority of the Regional Representative Council in Article 22D of the Constitution of the Republic of Indonesia . The steps taken in collecting data were collecting books related to the existence of the authority of the Regional Representative Council in article 22 D of the 1945 Constitution and classifying existing data in books or reading material that are related to the problem under study accordingly. with the necessary requirements . Furthermore, the data obtained were analyzed using descriptive analysis techniques.